Diversification expansion strategies: their impact on profitability in retail sector in Zimbabwe - Marry Murambi; Onwards Orpah Chivivi; Chipo Mutongi (EPRA Journals, 2023)
The study analysed the impact of diversification expansion strategy on profitability in grocery retail sector. Glueck’s (1976) expansion strategy was used as the theoretical framework in this study to explain diversification expansion strategies. The study used quantitative approach with a sample size of 30% that consists of 30 participants drawn from the three retail companies; OK, Spar and TM Pick ‘n’ Pay.Regression and correlation analysis was used to find the relationship between diversification expansion strategy and profitability. The study found out that diversification was leading to differences in profit volumes by 37%. The study concluded addressing of problems in the diversification expansion strategy to avoid affecting profitability in the retail sector in Zimbabwe.